2016
DOI: 10.1080/10253890.2016.1203416
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial stress based on public speech in humans: is there a real life/laboratory setting cross-adaptation?

Abstract: Repeated or chronic exposure to stressors is associated with changes in neuroendocrine responses depending on the type, intensity, number and frequency of stress exposure as well as previous stress experience. The aim of the study was to test the hypothesis that salivary cortisol and cardiovascular responses to real-life psychosocial stressors related to public performance can cross-adapt with responses to psychosocial stress induced by public speech under laboratory setting. The sample consisted of 22 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…SC AUCg was about 22% larger on concert day than on the first three pre-concert days taken together, mainly due to higher sC levels on concert day between 2 pm and 9 pm. This finding is in line with studies investigating sC responses to music performances (e.g., Aufegger and Wasley, 2017;Halleland et al, 2009;Pilger et al, 2014) and other social-evaluative situations (e.g., Jezova et al, 2016;Rohleder et al, 2007;Wetherell et al, 2015), The heightened sC AUCg observed on concert day in the present study cannot be explained by physical demands of performing for 5-10 min because the duration and intensity of physical exertion associated with the concert were below the thresholds required to stimulate cortisol release (Aufegger and Wasley, 2017;Strahler et al, 2017). SC AUCg on concert day and on the last pre-concert day were not significantly different from each other.…”
Section: Discussionsupporting
confidence: 90%
“…SC AUCg was about 22% larger on concert day than on the first three pre-concert days taken together, mainly due to higher sC levels on concert day between 2 pm and 9 pm. This finding is in line with studies investigating sC responses to music performances (e.g., Aufegger and Wasley, 2017;Halleland et al, 2009;Pilger et al, 2014) and other social-evaluative situations (e.g., Jezova et al, 2016;Rohleder et al, 2007;Wetherell et al, 2015), The heightened sC AUCg observed on concert day in the present study cannot be explained by physical demands of performing for 5-10 min because the duration and intensity of physical exertion associated with the concert were below the thresholds required to stimulate cortisol release (Aufegger and Wasley, 2017;Strahler et al, 2017). SC AUCg on concert day and on the last pre-concert day were not significantly different from each other.…”
Section: Discussionsupporting
confidence: 90%
“…The current study examinded the content validity in terms of item content validity index (I-CVI) and content validity ratio (CVR) for the items of the suggested public speaking stress scale (PSSS). The findings indicated that most items have been accepted ; some items may need to be modified (items numbered 3,6,13,15) ; and the only item that was to be deleted according to the content validity evaluation was item number 7 as it had I-CVI less than 0.7 (table 1) .…”
Section: Resultsmentioning
confidence: 99%
“…Public speaking is speaking in front of an audience in order to affect them ; whivh may include the negative experience of stress while speaking and the detrimental effects on speech performance (2) . The source of psychosocial stress can be explained by the task of standing and speaking in front of an large strange professional audience; this situation is stressful enough to trigger wide neural and hormonal responses throughout activation of the hypothalamic pituitary adrenal axis (3) . The stressor elicit the activation of the sympathetic autonomic nervous system, which promotes the release of adrenaline (epinephrine) and noradrenaline (norepinephrine) from the adrenal medulla.…”
Section: Introductionmentioning
confidence: 99%
“…Human clinical and rodent studies shed new light on possible biomarkers of stress-related disease (Strac et al, 2016;Tseilikman et al, 2016) and on understanding the role of experiential factors in determining stress coping. Adaptation and stress coping were also addressed in a study in students of dramatic arts, showing that neuroendocrine responses to real-life stressors in actors can partially crossadapt with responses to psychosocial stress in a laboratory setting (Jezova et al, 2016).…”
Section: Editorialmentioning
confidence: 99%